Laparoscopic Groin Hernia Repair with TAPP: Experience at a Tertiary Level Hospital - Malla, Srijan; Rayamajhi, Jyoti; Bhat, Pawan Singh; Amatya, Bishwo Ram; Rawal, Sushil Bahadur (Medical Journal of Shree Birendra Hospital, 2018)
Background: Groin hernia represents a significant volume of workload at the department of surgery, Shree Birendra Hospital constituting about 25% of total general surgical operations annually. Regular laparoscopic repair is now being done at the hospital. Hence, a retrospective study was performed to assess safety, feasibility, return to work and associated complication during the learning curve. Method: A single institution, single unit retrospective study of all TAPP hernia repair performed at the department of surgery from Dec 2016 to Nov 2017. Data of all patients undergoing TAPP were obtained from a proforma attached to the case file during patients’ admission and retrospectively analyzed. Results: A total number of 41 patients underwent the surgery including three bilateral hernias giving a total of 44 TAPPs being performed during the study period. Age group varied from 19 years to 72 years and a male dominance with 40 males to one female. Four patients underwent surgery for recurrent hernia following open surgery. Per operative findings of indirect hernia was noted in 39, direct in 4 and femoral in the only female patient. Duration of surgery ranged from 128 mins to 47 mins with progressively decreasing time in the second half of the study period. Complications encountered in the post-operative period were seroma in four patients, peritonitis in one and recurrence in one patient. Patients were discharged in median two days with the serving soldiers sent back to their respective units in median 7 days. Conclusion: Laparoscopic repair of groin hernias can safely be carried out in our settings with the TAPP method with all the established advantages of a minimal access surgery.